Physical condition profile of high-achieving university students in kickboxing - Siahaan, Jurdan Martin; Susanto, Ratno (Jurnal Ilmu Keolahragaan, 2025)
Background. Kickboxing is a combat sport that requires a high level of physical fitness to achieve optimal competitive performance. University student-athletes face unique challenges in balancing academic responsibilities and athletic achievement, making scientific evaluation of their physical condition essential. Objectives. This study aimed to analyze the physical condition profile and its relationship with kickboxing achievement among high-performing university student-athletes. Methods. This research employed a quantitative descriptive-correlational design. The participants were 20 kickboxing student-athletes selected using purposive sampling. Data were collected through physical fitness tests, including muscular strength, lower limb explosive power, speed, and cardiorespiratory endurance (VO₂max). Achievement data were obtained from official competition records. Descriptive statistics and Pearson correlation analysis were used to analyze the data. Results. The results showed that the overall physical condition of kickboxing student-athletes was categorized as very good, with an average percentage score of 85.1%. Most participants were classified in the very good physical condition category (55%), followed by good (35%) and fair (10%). In terms of achievement, the majority of student-athletes demonstrated high achievement levels (45%), while 30% reached very high and 25% moderate achievement categories. Conclusion. Correlation analysis indicated a positive and significant relationship between physical condition components and kickboxing achievement, particularly lower limb explosive power, speed, and cardiorespiratory endurance. In conclusion, physical condition plays a crucial role in supporting kickboxing achievement among university student-athletes. These findings suggest that well-structured, evidence-based training programs are essential to enhance performance while accommodating the academic demands of university athletes.